High-concentrate diet supplemented with hydrolysable tannin improves the slaughter performance, intestinal antioxidant ability and barrier function of fattening lambs - Ma, Jian; Li, Tao; Lin, Lu; Lu, Yuezhang; Chen, Xi; Li, Sibing; Wei, Chen; Du, Chunmei; Yin, Fuquan; Cao, Guang; Gan, Shangquan (Frontiers in Veterinary Science, 2024)
The objective of current experiment was to study the potential influence of hydrolysable tannin supplementation on slaughter performance, meat quality, intestinal digestive enzyme activity, antioxidant ability and barrier function in fattening lambs. In total, 36 male Hu sheep lambs with similar body weight (15.83 ± 0.48 kg) and days in age (55 ± 2 d) were randomly assigned to one of three groups of 12 animals each: control without tannin (CON) and tannin supplementation groups (TA1, 3 g/d per lamb; TA2, 6 g/d per lamb). All the lambs were reared in individual hutches, and the experiment lasted for 60 d. On d 61, 8 lambs from each group were randomly selected to slaughter. Results showed that the serum diamine oxidase and lipopolysaccharide contents of TA2 group were higher (p < 0.05) than those of CON group. Compared with CON group, the carcass weight and intramuscular fat content of lambs in TA1 group were increased (p < 0.05) and the meat shear force was decreased (p < 0.05). The trypsin activity in the jejunum and ileum of TA1 group was higher (p < 0.05) than that of CON and TA2 groups. Also, tannin supplementation significantly increased (p < 0.05) the level of jejunal and ileal total antioxidant capacity and reduced (p < 0.05) the jejunal malondialdehyde concentration in lambs. The jejunum and ileum of TA1 lambs showed reduced (p < 0.05) tumor necrosis factor-alpha and increased (p < 0.05) interleukin-10 mRNA levels compared with CON lambs. In the jejunum, the secretory immunoglobulin A content of TA1 group was higher (p < 0.05) than that of CON and TA2 groups. Lambs supplemented with tannin at the level of 3 g/d increased (p < 0.05) the gene expressions of claudin-1, claudin-4 and zonula occludens-1 in the jejunum when compared to those of CON and TA2 groups. In summary, tannin supplementation at the level of 3 g/d per animal can improve the production performance and intestinal function of fattening lambs fed a high-concentrate diet.